Global Events and Local Narratives: 9/11 and the Picture Storytellers of Bengal. - Chatterji, Roma (Indian Folklore Research Journal, 2009)
This paper will examine the relativity of contexts produced through diverse mechanisms for interaction by using the example of the picture storytellers of Bengal (Chitrakaras) and their narrative scroll paintings depicting the 9/11 strikes at the World Trade Centre in New York. The Chitrakaras display the scroll along with a narrative constructed from newspaper and television reports and from other popular art forms such as the jatra. The narrative reveals a structure resembling the mythical narrative form mangala kavya that anchors the 9/11 event in a context that is locally intelligible and acceptable. Unlike other forms of mass media this traditional method of storytelling has the receptors actively participating in re-interpreting the event by re-locating it in mythical time. But myths cannot be self-consciously produced, they can only be re-produced or re-enacted. When retold as a myth, the 9/11 story does lose some of the unique features that make it a historic event. What it does acquire is a more universalistic dimension by focusing on human dilemmas and emotions. Thus the universal appeal of the Laden pata, even to those who are not familiar with the narrative tradition within which it is located, can be said to emanate from its ability to re-locate the global event in a local moral context.